2005
DOI: 10.1177/0266666905060089
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technologies in Small and Medium Scale Tourism Enterprises in Durban, South Africa

Abstract: The objectives of this paper are to identify factors influencing the adoption of innovations, specifically e-commerce readiness and to identify specific barriers or obstacles to the use of ICT by small and medium tourism enterprises in Durban, KwaZulu-Natal Province, South Africa. Enterprises studied included guesthouses, lodges and self-catering, bed and breakfast, and tour operators. A survey research design was adopted and data collected through interviews, observation and administration of a structured que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Such information can be used to design websites that attract more users, target specific markets, and display features customized to individual interests. These results are in line with the study conducted by Migiro and Ocholla (2005) on the use of e-commerce tools in tourism SMEs in KwaZulu-Natal province, where they established that one of the main reasons why SMEs adopt e-commerce tools was to reach new customers. An earlier study by Thanasankit (2002:200) established that the Internet lowers the cost of market research.…”
Section: Reasons For E-commerce Adoptionsupporting
confidence: 90%
“…Such information can be used to design websites that attract more users, target specific markets, and display features customized to individual interests. These results are in line with the study conducted by Migiro and Ocholla (2005) on the use of e-commerce tools in tourism SMEs in KwaZulu-Natal province, where they established that one of the main reasons why SMEs adopt e-commerce tools was to reach new customers. An earlier study by Thanasankit (2002:200) established that the Internet lowers the cost of market research.…”
Section: Reasons For E-commerce Adoptionsupporting
confidence: 90%
“…Karanasios (2008) stressed that under high global competition, travel and tourism agencies cannot survive without continuity and achieve economies of scale, which help reduce operational costs and gain marketing force, which would not be possible without the optimal use of Internet services. Migiro and Ocholla (2005) explained in their study that Internet applications in the tourism services industry has led to an almost complete change in the purchasing behavior of tourism services. By using the Internet as a marketing channel, working seven days a week and 24 hours a day, tourism customers may choose products and services without the intervention and influence of salesmen.…”
Section: Internet In Saudi Arabiamentioning
confidence: 99%
“…Stansfield and Grant, 2003b;Warden and Tunzelana, 2004 Ayeh, 2006;Chen and McQueen, 2008;Heung, 2003;Kula and Tatoglu, 2003;Simmons et al, 2008;Grant, 2003a, 2003b;Stockdale and Standing, 2006;Zheng et al, 2004. Lack of technical knowledge of what and how to adopt a certain technology Kartiwi and MacGregor, 2007;Migiro and Ocholla, 2005;Mirchandani and Motwani, 2001;Scarborough and Zimmerer, 2003;Warden and Tunzelana, 2004;Webster et al, 2006 Available resources Inadequate financial resources Ayeh, 2006;Grandon and Pearson, 2004;Jin, 2007;Migiro and Ocholla, 2005;Skoko et al, 2008;Stansfield and Grant, 2003b;Stockdale and Standing, 2006;Zheng et al, 2004 High costs of technology adoption: technologies and equipment Ayeh, 2006;Beck et al, 2005;Chen and McQueen, 2008;Ghamatrasa, 2006;Migiro and Ocholla, 2005;Mirchandani and Motwani, 2001;Pilat, 2003;Rao et al, 2003;Wahid, 2007;Webster et al, 2006 High cost of developing and managing websites Anckar, 2003;Kula and Tatoglu, 2003;MacGreogor and Vrazalic, 2005;Nour, Dyerson and Harindranath, 2007;Ghamatrasa, 2006;Kamel and Hussei...…”
Section: External Boundariesmentioning
confidence: 99%
“…On the other hand, as cited in many past studies, there are many factors found to have negatively influenced technology adoption in SMEs; examples are cost of technology implementation (Kuan and Chau, 2001;MacGreogor and Vrazalic, 2005;Migiro and Ocholla, 2005;Kim, 2006), limited resources of SMEs (Stockdale and Standing, 2006;Skoko et al, 2008), infrastructure and technological readiness (Ayeh, 2006;Azam, 2007;Wahid, 2007), lack of skilled labour (Warden and Tunzelana, 2004;Samoilenko and Osei-Bryson, 2008), cultural issues (Dutta and Coury, 2003;Zheng et al, 2004), the required time for change (Heung, 2003;Wahid, 2007), service/product/customer/ supplier suitability (Tucker, 2008), legal and security issues (Buhalis and Laws, 2001;Nour, 2002;Kula and Tatoglu, 2003), and adopted technology related factors (Kendall et al, 2001;Beckinsale and Levy, 2004;Dyerson and Harindranath, 2007). For this study, these factors will be labelled as "boundaries" which hinders technology adoption in SMEs.…”
Section: Introductionmentioning
confidence: 99%